Prediksi Ketertarikan Siswa Dalam Ketepatan Nilai KKM Pada Mata Pelajaran TIK Tingkat Sekolah Dasar Pada Sekolah Dasar KITRI BAKTI Menggunakan Algoritma C.4.5 - herman herman suherman (Jurnal Pelita Teknologi, 2021)
The advancement rapid of information and communication technology (ICT) today, along with technological developments also have reached the field of education. Data Mining is currently one of the centers of attention in academics and practitioners, with the data control we can know the level of learning process or the percentage in every year before which can be used as a reference of learning process in coming year. Therefore, the authors make predictions of students interest in accuracy of primary school KKM standard with this prediction, it can be useful for schools to know the value of students KKM as well as restrictions on student benchmarks in order to exceed the predetermined value. Data mining prediction is done by searching the data in previous year with Microsoft excel, the development of data mining using algorithm C4.5 with accuracy obtained by decision tree and make application of prediction Rule of data mining by using PHP Keywords Data Mining Prediction, Algorithm C4.5, Decision Tree, PHP, Waterfall .